Patterns of seasonality and group membership characterize the gut microbiota in a longitudinal study of wild Verreaux's sifakas (Propithecus verreauxi). Issue 15 (15th June 2017) - Springer, Andrea; Fichtel, Claudia; Al‐Ghalith, Gabriel A.; Koch, Flávia; Amato, Katherine R.; Clayton, Jonathan B.; Knights, Dan; Kappeler, Peter M.
Abstract: The intestinal microbiota plays a major role in host development, metabolism, and health. To date, few longitudinal studies have investigated the causes and consequences of microbiota variation in wildlife, although such studies provide a comparative context for interpreting the adaptive significance of findings from studies on humans or captive animals. Here, we investigate the impact of seasonality, diet, group membership, sex, age, and reproductive state on gut microbiota composition in a wild population of group‐living, frugi‐folivorous primates, Verreaux's sifakas ( Propithecus verreauxi ). We repeatedly sampled 32 individually recognizable animals from eight adjacent groups over the course of two different climatic seasons. We used high‐throughput sequencing of the 16S rRNA gene to determine the microbiota composition of 187 fecal samples. We demonstrate a clear pattern of seasonal variation in the intestinal microbiota, especially affecting the Firmicutes‐Bacteroidetes ratio, which may be driven by seasonal differences in diet. The relative abundances of certain polysaccharide‐fermenting taxa, for example, Lachnospiraceae, were correlated with fruit and fiber consumption. Additionally, group membership influenced microbiota composition independent of season, but further studies are needed to determine whether this pattern is driven by group divergences in diet, social contacts, or genetic factors. In accordance with findings in other wild mammals and primates with seasonally fluctuating food availability, we demonstrate seasonal variation in the microbiota of wild Verreaux's sifakas, which may be driven by food availability. This study adds to mounting evidence that variation in the intestinal microbiota may play an important role in the ability of primates to cope with seasonal variation in food availability. Abstract : This study provides insights into commensal microbial ecology by assessing gut microbiota variation in a wild population of group‐living, frugi‐folivorous lemurs, which are subjected to strong seasonal variation in food availability. Comparison of samples taken from 32 individuals belonging to eight adjacent social groups during the dry and during the wet season suggests a strong effect of diet on microbiota composition. Furthermore, the eight social groups diverged in microbiota composition across the study period, suggesting that additionally to macroecological patterns, either small‐scale variation in diet/habitat or host genetic and social factors, shape commensal microbial communities.